Quantitative analysis of three-dimensional-resolved fiber architecture in heterogeneous skeletal muscle tissue using nmr and optical imaging methods. - Napadow, V J (2001)
The determination of principal fiber directions in structurally heterogeneous biological tissue substantially contributes to an understanding of its mechanical function in vivo. In this study we have depicted structural heterogeneity through the model of the mammalian tongue, a tissue comprised of a network of highly interwoven fibers responsible for producing numerous variations of shape and position. In order to characterize the three-dimensional-resolved microscopic myoarchitecture of the intrinsic musculature of the tongue, we viewed its fiber orientation at microscopic and macroscopic length scales using NMR (diffusion tensor MRI) and optical (two-photon microscopy) imaging methods. Diffusion tensor imaging (DTI) of the excised core region of the porcine tongue resulted in an array of 3D diffusion tensors, in which the leading eigenvector corresponded to the principal fiber orientation at each location in the tissue. Excised axially oriented lingual core tissues (fresh or paraffin-embedded) were also imaged with a mode-locked Ti-Sapphire laser, (76 MHz repetition rate, 150 femtosecond pulse width), allowing for the visualization of individual myofibers at in situ orientation. Fiber orientation was assessed by computing the 3D autocorrelation of discrete image volumes, and deriving the minimal eigenvector of the center voxel Hessian matrix. DTI of the fibers, comprising the intrinsic core of the tongue, demonstrated directional heterogeneity, with two distinct populations of fibers oriented orthogonal to each other and in-plane to the axial perspective. Microscopic analysis defined this structural heterogeneity as discrete regions of in-plane parallel fibers, with an angular separation of ~80 degrees, thereby recapitulating the macroscopic angular relationship. This analysis, conceived at two different length scales, demonstrates that the lingual core is a spatially complex tissue, composed of repeating orthogonally oriented and in-plane fiber patches, which are capable of jointly producing hydrostatic elongation and displacement.